New Genre Arctic Art and Art Education Exhibition : Playing With Snow In the Endangered Winter, 2024 - Stöckell, Antti (Stormen Concert Hall, 2024)
As climate change progresses, the way of life and livelihoods dependent on winter and snow are in the throes of change. I organize winter art workshops at the University of Lapland, Faculty of Art and Design. Snow and winter are also central elements of my personal art. The need for deal with climate and winter change experiences grows every year. In teaching, we have paid attention to typical place-specifc snow sculptures in midwinter. Personally, in my own art I have been looking for ways of working with snow throughout the winter. The possibilities of varying the methods of making winter art seem almost limitless. Making the experimental winter art offers situations for the growth of winter related natural scientifc, cultural and aesthetic understanding, knowledge and skill. When practicing and developing on winter art in all kinds of conditions becomes continuous, the handling of concerns related to climate change can also become stronger.